Il portale GeoNetwork di SHARE Un catalogo condiviso di metadati a servizio delle ricerche in alta montagna - Melis, Maria Teresa; Busilacchio, Marcella; Di Carlo, Piero; Vuillermoz, Elisa; Bonasoni, Paolo (GEOmedia, 2011)
Il progetto SHARE (Stations at High Altitude for Research on the Environment) del Comitato Ev-K2-CNR promuovela realizzazione di un servizio di accesso alle ricerche dedicate agli ambienti di alta quota attraverso la piattaformaGeoNetwork. La condivisione di dati e metadati che avviene attraverso l'ambiente dedicato, di cui questo articolopresenta la prima fase di realizzazione, permette alla comunità scientifica e all'utente interessato di seguire lostato delle conoscenze ambientali in tema di cambiamenti climatici anche attraverso l'accesso diretto ai dati. SHARE GeoNetwork portal, a shared catalog of metadata for research in high mountain The need to share information and data in science finds a ready answer in new technology in the development of Internet access services structured ac-cording to standards that guarantee the accessibility to the scientific community. In this context it is being realized at the Ev-K2-CNR Commitee a platform for web services based on the architecture of GeoNetwork Opensource for the re-alization of the data and metadata cata-log dedicated to the high altitude re-search. This activity is one of the themes of scientific and technological research project SHARE (Stations at High Altitude for Research on the Environment). The first phase of the project was dedicated to the completion of the cataloging system of climate observatories and weather stations in high mountain re-gions included in the SHARE program that acquire the data, some of which are transmitting from the highest peaks in the world, and available in real time for the SHARE researchers and the scientific community.